Enzymes involved in immunity and characteristics of hemolymph in red sternum syndrome mud crabs (Scylla serrata) - Kankamol, Chantana; Salaenoi, Jintana (Agriculture and Natural Resources, 2018)
The activities were compared of the immunological enzymes phenoloxidase (PO) and superoxide dismutase (SOD) and the concentration of proteins and urea nitrogen (UN) in the hemolymph of red sternum syndrome mud crabs, Scylla serrata, (Forskål, 1755) (Decapoda: Portunidae), with those of normal crabs. Twenty-five red sternum mud crabs and 10 normal mud crabs were randomly collected from crab farms in Samut Songkram province, Thailand. Statistical analysis used the mean ± SD and Student's t test at a significance level of α = 0.05. Levels of PO were 0.032 ± 0.013 units/mg protein and 0.075 ± 0.028 units/mg protein, while SOD levels were 0.493 ± 0.079 units/mg protein and 1.464 ± 0.783 units/mg protein, in normal and red sternum mud crabs, respectively. There was a significant difference in enzyme activities between the two groups. The hemolymph protein concentration in normal crabs was 1.03 ± 0.20 mg/mL which was significantly higher than in red sternum syndrome crabs (0.66 ± 0.23 mg/mL). The UN level in the hemolymph of normal mud crabs was significantly higher (10.78 ± 3.96 mg/dL) compared with that of red sternum mud crabs (4.59 ± 1.57 mg/dL). The findings revealed that the protein and UN levels in the hemolymph of red sternum mud crabs had decreased significantly. The red sternum syndrome was inversely related to the accumulated amount of protein and UN in crabs and had an extreme effect on protein metabolism.